Tracing Sinbad’s heroic path in Naguib Mahfouz’s Layālī Alf Laylah: A Narrative perspective of Christopher Vogler - Khotimah, Husnul; Masadi, M. Anwar (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
Heroic narratives have always held a universal appeal as they portray the human struggle in facing life’s challenges while simultaneously seeking the deeper meaning of existence. This study aims to examine the heroic journey of Sinbad in Naguib Mahfouz’s Layālī Alf Laylah through the narrative framework of the Hero’s Journey as developed by Christopher Vogler. The research focuses on two main aspects: identifying the stages of Sinbad’s transformation and revealing the archetypes that shape the narrative structure. A descriptive qualitative method was employed, utilizing close reading, data annotation, and the Miles and Huberman interactive model of analysis, which includes data reduction, data display, and conclusion drawing. The findings reveal that although Vogler’s Hero’s Journey model comprises twelve stages, Sinbad undergoes only ten of them. These stages include the ordinary world, meeting with the mentor, crossing the first threshold, test allies and enemies, approach, supreme ordeal, reward, the road back, resurrection, and return with the elixir. This indicates that Sinbad’s heroic path does not strictly follow a linear pattern but rather adapts to the narrative context shaped by Mahfouz. Unlike earlier studies that often relied on Joseph Campbell’s monomyth, this research demonstrates that Vogler’s model being more structural, cinematic, and character centered provides a more dynamic and context-sensitive lens to interpret both the external adventure and inner transformation of the hero in Arabic narrative tradition. This distinction is significant because it extends the applicability of Western narrative theory to Arabic literature in a more flexible and culturally resonant way, revealing how Mahfouz’s adaptation of the heroic pattern blends universal motifs with local moral and spiritual dimensions. These findings affirm that Mahfouz does not merely present an external adventure but also constructs an inner journey imbued with moral, spiritual, and existential values. This research contributes to the development of modern Arabic literary studies by applying Vogler’s narrative model and offers a fresh perspective on the representation of heroism. Ultimately, Sinbad’s journey illustrates that heroism transcends external triumphs and is equally defined by profound inner transformation, resonating across cultures and generations.